Analisis Kinerja Pembangunan Provinsi Nusa Tenggara Barat Dalam Aspek Kesejahteraan, Ketimpangan, Pembangunan Manusia, Pendidikan Dan Kesempatan Kerja - Wahidin, Wahidin; Sahri, Sahri; Karismawan, Putu; Firmansyah, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
This study aims to: examine the effect of Government Expenditures The scope of this study evaluates the development performance of the province of Nusa Tenggara Barat with the objective to mengeatahui economic prosperity of the population, income inequality among the population, human development progress, education participation of the population, and labor force participation. Research variables: per capita income (PDRB per capita), number of households, household income, ie harapa life rate, literacy rate, school participation rate (APS), rough participation rate (APK), and net enrollment rate (APM) , the population of the working labor force, the working age population. Data of research variables using time series data (time series) last five years. Data analysis using descriptive statistical analysis. Result of research: level of economic prosperity of society increase from year to year. Despite the increase but the economic welfare of NTB population is still below the economic welfare level of the population of the provinces in the West Indonesia region. The inequality of income distribution between urban and rural population is at a moderate level of inequality. The growth rate of NTB's HDI is highest in Indonesia, but still ranks 30 out of 34 provinces in Indonesia. The education participation rate of NTB population is above ninety percent. The labor force participation rate of NTB population has increased and has reached the figure of seventy percent.